RUTE TERPENDEK UNTUK PENGANGKUTAN SAMPAH DENGAN PENDEKATAN LINTASAN HAMILTON - ROZI, SYAMSYIDA; MULTAHADAH, CUT (E-Jurnal Matematika; Vol 10 No 2 (2021), 2021)
This research is related to the route of picking up the waste which done by janitors in housing complex of Aur Duri Indah Rt.14 Jambi considering the condition of that housing which have some crossroads, such that janitors take the same road twice which seems inefficient in terms of time and fuel consumption. This research is aimed to identify scientifically about the shortest and more efficient route which should be taken by janitors. This problem is considered as optimization problem through graph modelling. To check the efficient route, the existence of Hamiltonian Path of the graph is identified by using Depth-First Search method, and so is the shortest path. It is found that there are 39 Hamiltonian paths and the shortest path has total distance of 793.8 meter. By the existence of the shortest Hamiltonian Path, it is confirmed that janitors in housing complex of Aur Duri Indah Rt.14 can travel each road once with total distance is about 793.8 meter.